PENGGUNAAN MEDIA LETS COUNTING UNTUK MENSTIMULASI KEMAMPUAN MENGENAL HURUF ANAK USIA DINI DI KB PAROPA - Nurtinah; Ahmadin; Haris, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to recognize letters is a crucial foundation for early literacy development in young children. Based on initial observations at Paropa Kindergarten, it was found that some children still struggled to distinguish between the shapes and sounds of letters and lacked motivation to learn due to monotonous teaching methods. To address these issues, the teacher implemented an innovative teaching approach using the “Let’s Counting” media, which was designed to be interactive and engaging to stimulate the children’s letter recognition skills. This study aims to describe the implementation and effectiveness of the “Let’s Counting” media in improving young children’s ability to recognize letters. This study employs a qualitative research design with a descriptive approach. Data sources consisted of teachers and children in the playgroup at KB Paropa. Data collection techniques included observation, interviews, and documentation. The research procedure comprised three stages: planning, implementation, and evaluation of learning activities using the “Let’s Counting” media. The data analysis technique used the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The research results show that the use of the “Let’s Counting” educational media proved effective in stimulating early childhood letter recognition skills. Children demonstrated improvement in recognizing letter shapes and sounds through activities such as playing with letter cards, guessing letters, and integrative activities related to daily life. The learning process became more active, interactive, and meaningful. This educational tool not only fosters children’s interest in learning but also develops their cognitive, language, and social skills in an integrated manner.